PERKEMBANGAN LEMBAGA PENDIDIKAN MADRASAH DI INDONESIA: SEBUAH TINJAUAN SEJARAH PENDIDIKAN - Niswah, Choirun; Pratama, Cahyadi; Rifany, Ika Nurfajriah; Rigi, Annisa Kiara (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2025)
ABSTRACT This article examines the development of madrasah educational institutions in Indonesia from the perspective of educational history. Madrasahs as Islamic educational institutions have an important role in the process of forming the national education system, especially in the integration of religious and general education. This study uses a descriptive qualitative approach with a literature study method on historical sources, laws and regulations, and related academic literature. The results of the study indicate that madrasahs have undergone significant transformations since the colonial era to the reform era, both in terms of curriculum, management, and institutional status. These changes are influenced by socio-political dynamics, government policies, and the needs of the Muslim community for holistic education. This study emphasizes the importance of historical understanding in formulating more adaptive and competitive madrasah education policies in the future. Thus, mapping the historical development of madrasahs serves as a strategic foundation for strengthening their role as a pillar of Islamic education that remains relevant to contemporary challenges. ABSTRAK Artikel ini mengkaji perkembangan lembaga pendidikan madrasah di Indonesia dari perspektif sejarah pendidikan. Madrasah sebagai institusi pendidikan Islam memiliki peran penting dalam proses pembentukan sistem pendidikan nasional, khususnya dalam integrasi antara pendidikan agama dan umum. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka terhadap sumber-sumber historis, peraturan perundang-undangan, dan literatur akademik terkait. Hasil kajian menunjukkan bahwa madrasah telah mengalami transformasi signifikan sejak masa kolonial hingga era reformasi, baik dari sisi kurikulum, manajemen, maupun status kelembagaan. Perubahan ini dipengaruhi oleh dinamika sosial-politik, kebijakan pemerintah, dan kebutuhan masyarakat Muslim terhadap pendidikan yang holistik. Kajian ini menegaskan pentingnya pemahaman historis dalam merumuskan kebijakan pendidikan madrasah yang lebih adaptif dan berdaya saing di masa depan. Dengan demikian, pemetaan sejarah perkembangan madrasah menjadi landasan strategis dalam memperkuat peranannya sebagai pilar pendidikan Islam yang relevan dengan tantangan zaman.